IMPORTANCE OF RATIONAL LIGHTING OF INDUSTRIAL PREMISES - N. M. Bakhriddinova (Western European Studies, 2024)
The work studies the importance of rational lighting of industrial premises, lighting requirements, types of lighting, and natural lighting standards. The characteristics of natural and artificial lighting, special requirements for artificial lighting are given. The factors influencing the lighting requirements are widely covered
Keywords: Lighting; Characteristics Of Natural And Artificial Lighting; Incandescent Lamps And Fluorescent Lamps